Curriculum Fidelity in the Secondary Education in Indonesia - Allo, Markus Deli Girik (International Journal of Psychosocial Rehabilitation, 2020)
It is significant that the educational plan of 2013 actualized with adequate constancy, consistency, recurrence, and force to guarantee an understudies’ dominance of the material, and to make understudies more picks up when instructors steadfastly execute the showing systems or educational plan. The objective of this study is to reveal the Torajan Teachers’ Fidelity towards the implementation of curriculum of 2013. The researcher applied of qualitative method in this research. The instrument utilized in this exploration were interview, the researcher interview the teachers by using semi-structured interview. The subjects of this research were 20 teachers in Toraja. The consequence of this study indicated that for Adherence, the educators did not follow well the methodology of the educational program of 2013 as depicted and executing all bits of the intercession in the erroneous request. It brought about by lacking preparation for the restoration educational program. For Exposure/duration, because the teacher focused on understanding of implementing the renewal curriculum, so, they need to suit the time estimation in the class, and sometimes, the time used more than the concept in lesson or vice versa. For quality of program delivery, teachers encountered of problem in teaching while observing the affective of all students. They tried to be focused on delivering the material but neglecting the affective assessment. For participant responsiveness, the students felt happy and got to be enthusiastic in the classrooms while the program running. But, in the several previous meetings, the students looked confused because the teacher seemed unsure with the implementation of that curriculum of 2013 (K13). For program differentiation, the teachers in Torajan context did not fully implement the program of curriculum of 2013, they still mixed the previous curriculum with the renewal one, Moreover, and they still used the traditional method in teaching.